2021
DOI: 10.3390/agronomy11102036
|View full text |Cite
|
Sign up to set email alerts
|

Global Distributions of Clarireedia Species and Their In Vitro Sensitivity Profiles to Fungicides

Abstract: Dollar spot is reported to be caused by multiple Clarireedia species and is a serious problem on many turfgrasses around the world. To our knowledge, the distribution of different Clarireedia species and their sensitivity profiles to fungicides remains unknown. In this study, a total of 275 isolates were characterized by ITS sequence. Amounts of 124, 59 and 75 isolates were identified as C. jacksonii, C. monteithiana and C. paspali, respectively, while each species of C. homoeocarpa and C. bennettii had only f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In a previous study, we found that multiple species of Clarireedia co-existed in a few golf courses, 7,10 which was further confirmed in the present study by the multiplex PCR method. For example, C. paspali, C. monteithiana and C. hainanense were detected in ML and SGL, and C. paspali and C. hainanense were detected in SZBD in both studies (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In a previous study, we found that multiple species of Clarireedia co-existed in a few golf courses, 7,10 which was further confirmed in the present study by the multiplex PCR method. For example, C. paspali, C. monteithiana and C. hainanense were detected in ML and SGL, and C. paspali and C. hainanense were detected in SZBD in both studies (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…5,7 Studies have revealed that multiple species in the genus Clarireedia co-exist on the same hosts or at same locales, which might complicate the management of DS disease. 5,7,9,10 Because morphological differences were observed among different species of Clarireedia, including pigment accumulation, oxalic acid production, pathogenicity and fungicide sensitivity, 7,10 it is indicated that different management strategies should be used to control DS disease caused by different species. Therefore, it is necessary to monitor the distributions and prevalence of different species in Clarireedia, especially at those locales where more than two species co-exist.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations